Political power and social theory. Vol. 16 - Davis, Diane E., 1953- (JAI, 2004)
This volume of "Political Power and Social Theory" addresses some of the most pressing questions of our times, from the origins and meaning of the war in Iraq to the transnational politics of immigration to the impact of race on labor organization to the historical underpinnings of corporate power. With careful attention to historical detail, with a keen eye for the value of inter-disciplinary social science inquiry, and with a view to various countries around the globe, this research annual once again unveils the complex dynamics of key contemporary and historical dilemmas that motivate citizens and scholars alike to struggle for a better future.